WW Domain-Containing Proteins YAP and TAZ in the Hippo Pathway as Key Regulators in Stemness Maintenance, Tissue Homeostasis, and Tumorigenesis - Chen, Yu-An; Lu, Chen-Yu; Cheng, Tian-You; Pan, Szu-Hua; Chen, Hsin-Fu; Chang, Nan-Shan (Frontiers in Oncology, 2019)
The Hippo pathway is a conserved signaling pathway originally defined in Drosophila melanogaster two decades ago. Deregulation of the Hippo pathway leads to significant overgrowth in phenotypes and ultimately initiation of tumorigenesis in various tissues. The major WW domain proteins in the Hippo pathway are YAP and TAZ, which regulate embryonic development, organ growth, tissue regeneration, stem cell pluripotency, and tumorigenesis. Recent reports reveal the novel roles of YAP/TAZ in establishing the precise balance of stem cell niches, promoting the production of induced pluripotent stem cells (iPSCs), and provoking signals for regeneration and cancer initiation. Activation of YAP, for example, results in expansion of progenitor cells, which promotes regeneration after tissue damage. YAP is highly expressed in self-renewing pluripotent stem cells. Overexpression of YAP halts stem cell differentiation and yet maintains the inherent stem cell properties. A success in reprograming iPSCs by the transfection of cells with Oct3/4, Sox2 and Yap expression constructs has recently been shown. In this review, we update the current knowledge and the latest progress in the WW domain proteins of the Hippo pathway in relevance to stem cell biology, and provide a thorough understanding in the tissue homeostasis and identification of potential targets to block tumor development.